Stapes Surgery Outcomes in Patients With Concurrent Otosclerosis and Superior Semicircular Canal Dehiscence. Issue 7 (August 2020) - McClellan, Joseph; Nguyen, Anthony; Hamilton, Bronwyn; Jethanamest, Daniel; Hullar, Timothy E.; Gupta, Sachin
Abstract : Objective: To review outcomes of stapes surgery in patients with concurrent otosclerosis and superior semicircular canal dehiscence. Study Design: Retrospective case series. Setting: Tertiary referral center. Patients: Patients with concurrent otosclerosis and superior canal dehiscence, confirmed by computed tomography (CT) imaging. Intervention(s): Stapes surgery for conductive hearing loss. Main Outcome Measure(s): Postoperative air-bone gap (ABG), as well as the number of patients in whom surgery was deemed successful (postoperative ABG <10 dB HL). Results: Five patients with superior canal dehiscence and concomitant otosclerosis who underwent surgical repair were identified. Mean preoperative ABG was 29.0 ± 6.4 dB HL. Mean postoperative ABG was 13.0 ± 13 dB HL. Three patients (60%) had a successful outcome, defined as postoperative ABG less than 10. One patient experienced unmasking of superior canal dehiscence vestibular symptoms. Conclusions: Patients with concurrent otosclerosis and superior canal dehiscence appear to have a lower likelihood of successful hearing restoration following stapes surgery. Patients should be counseled accordingly. Routine preoperative CT imaging before stapes surgery may be helpful to identify patients at risk for poor outcomes.